Às margens da Margem: o cinema como prática de resistência, e os sujeitos deambulantes no filme de Ozualdo Candeias (1967-1970) - Silva, Edinei Pereira da (2019)
The objective of this dissertation and its scope is the study of the movie A Margem (The Edge), of the filmmaker Ozualdo Candeias, from the cinematographic movement called Cinema Marginal (Marginal cinema). It is a 1967’s film, conceived, mainly, from the perspective of the great changes that directly impacted São Paulo city and, consequently, is focused on bring the elements concerned with the process of metropolis’ urbanization, as long as the art issues of that moment, starting from the changes arising from the incessant capitalism advances and its interference in the environment, more specifically in the rivers and its tributaries – read Rio Tietê (Tiete river). Interferences perceived, also, in the artistic manifestations from that moment. In addition, this production points out the action of the insurgent marginalized subjects in the face of the challenges facing strength of a fragmented city, in other words, ordinary men in writing History from the everyday resistance, through the appropriation of art as a reporting mechanism. That is the meaning of sewing the events taking into account a History against the Grain. In short, it is proposed that the film concerned is a historical source capable of readings that transcends what is laid before our eyes, it goes beyond when reviews are made between the lines of everyday practices, by emphasizing the implicit tensions there